[Letter from Latino Peace Officers Association to Sen. Packwood opposing excise tax plan] (Tufts Archival Research Center, 2007)
Letter from the Latino Peace Officers Association to Sen. Packwood opposing the excise taxes in his tax plan. Labels Packwood's plan as "regressive and discriminatory towards the disadvantaged consumer." Urges Packwood to consider the negative impact his legislation would have on the Hispanic community.